Is It Easy to Do the Right Thing?: An Approach to Sustainable Development in Teacher Education in Sweden - Martina Wyszynska Johansson (Postscriptum Polonistyczne)
The essay deals with sustainable development in teacher education in Sweden. Using self-study of teacher educator praxis allows inquiry into practical experience informed by propositional knowledge. Using a curriculum theory approach, two dimensions of work on sustainable development at a university are presented, the intended and enacted curriculum. The intended curriculum is expressed in policy documents whereas the enacted dimension is exemplified by a Sustainable Development course addressing, among others, teacher educators at the current university. The two curriculum dimensions are well-aligned with one another. Policy documents ascribe the students and the teaching staff an active role as contributors to work on sustainable development from the point of view of three dimensions, environmental, social, and economic. The call for action dominates, and the rationale for the course is grounded in insights from natural and social sciences. The need to include insights from the humanities is proposed as they may enrich work on sustainable development with novel sensitivities. The essay invites teacher educators to discuss ways to prepare prospective teachers for work on sustainable development.